A systematic review of self-regulated learning in flipped classrooms: key findings, measurement methods, and potential directions - Silverajah, V. S. Giita; Wong, Su Luan; Govindaraj, Anandraj; Md. Khambari, Mas Nida; O. K. Rahmat, Rahmita Wirza; Mohd Deni, Ann Rosnida (IEEE, 2022)
Online instruction through a flipped classroom approach has continued to gain popularity in recent years. Engaging learners’ attention in achieving learning outcomes while embracing the flexibility of online learning via flipped classrooms remains an essential topic among educators, educational institutions, and society. Studies have found that students equipped with self-regulated learning strategies thrive in such learning environments. The present study describes and analyses the state of research in self-regulated learning strategies and their association with the flipped classroom based on the review of articles published in Q1 and Q2 journals from 2016 to the middle of 2021. The instructions in PRISMA guided the development of systematic review protocols. Thirty-two scientific texts from four search databases, Science Direct, Scopus, ERIC, and ProQuest, were reviewed. The key findings present the effects of self-regulation on academic and non-academic outcomes and the factors that influenced the outcomes. The findings also revealed six preferred methods to measure self-regulated learning in a flipped classroom, specifically through self-report questionnaires, as the most preferred approach, followed by learning analytics, interviews, think-aloud protocols, reflective documents, and observation. Furthermore, the potential future areas of study are detailed as prospect references. In conclusion, it is highly recommended for educators and future studies to integrate the essential characteristics of flipped learning as pointed out by the four pillars (F-L-I-P): flexible environment, learning culture, intentional content, and professional educator. Ultimately, this justifies the successful integration of the flipped classroom into learning and facilitates the development of self-regulated learning strategies.